The Cost Effectiveness of Donafenib Compared With Sorafenib for the First-Line Treatment of Unresectable or Metastatic Hepatocellular Carcinoma in China - Meng, Rui; Cao, Yingdan; Zhou, Ting; Hu, Hongfei; Qiu, Yijin (Frontiers in Public Health, 2022)
Background Recent clinical trials have demonstrated that donafenib has superior efficacy and safety compared with sorafenib in Chinese patients with unresectable or metastatic hepatocellular carcinoma (HCC). The objective of this study was to assess the cost effectiveness of donafenib compared with sorafenib for the treatment of patients with unresectable or metastatic HCC in China. Methods A three-state partitioned survival model was developed to perform a cost-effectiveness analysis comparing donafenib and sorafenib from a Chinese healthcare payer's perspective. The model adopted a lifetime horizon and a 4-week cycle length. Survival data were derived from the ZGDH3 study and fitted with standard parametric functions for extrapolation beyond the trial period. Cost data were obtained from the mean price of publicly listed online bids in 2021 and medical service prices across provinces in China. Utility data were obtained from previous literature. The cost and health outcomes were discounted at an annual rate of 5%. Deterministic and probabilistic sensitivity analyses (PSAs) were carried out to verify the robustness of the model. Results Compared with sorafenib, donafenib incurred a higher cost (US22,330.23 vs. US14,775.92) but yielded more quality-adjusted life years (1.045 vs. 0.861 QALYs). The incremental cost-effectiveness ratio (ICER) for donafenib was US41,081.52 per QALY gained (ICER = US13,439.10/QALY). The PSA results indicated that at a willingness-to-pay threshold of 3 times the GDP in China, the probability of donafenib being cost effective was 16.9%. The ICER (US13,439.10/QALY) decreased when the branded price of sorafenib was used in the model. Conclusions Donafenib is unlikely to be cost effective compared with sorafenib for the first-line treatment of unresectable or metastatic HCC in China. Reducing the price of donafenib can increase the possibility of it being cost effective in the future.